Proceedings of the Second International Conference on Theoretical, Applied and Experimental Mechanics - Gdoutos, Emmanuel E. (Structural Integrity, 2019)
This is the proceedings of the 2nd International Conference on Theoretical, Applied and Experimental Mechanics that was held in Corfu, Greece, June 23-26, 2019. It presents papers focusing on all aspects of theoretical, applied and experimental mechanics, including biomechanics, composite materials, computational mechanics, constitutive modeling of materials, dynamics, elasticity, experimental mechanics, fracture, mechanical properties of materials, micromechanics, nanomechanics, plasticity, stress analysis, structures, wave propagation. The papers update the latest research in their field, carried out since the last conference in 2018. This book is suitable for engineers, students and researchers who want to obtain an up-to-date view of the recent advances in the area of mechanics.